Responsibility of the state assets and auction services office (Kpknl) in the lawsuit for the implementation of the auction for the execution of mortgage rights - Nauw, Vernando Anderson William; Salmon, Hendrik; Lekipiouw, Sherlock (Institute Of computer Science (IOCS), 2024)
The role of the auction is quite large in meeting the needs of the community, with the principles of fairness, transparency / openness, legal certainty, accountability, and efficiency to provide another way of buying and selling at the best price which is characterized by competition between enthusiasts or prospective buyers. This research uses qualitative methods with primary data types. The results showed that the implementation of the auction by the KPKNL was in accordance with the Regulation of the Minister of Finance No. 213 /PMK.06/2020 concerning guidelines for the implementation of auctions, but there are still obstacles, namely auction participants do not understand the requirements of auction documents, lawsuits are made by the parties. debtors or owners of collateral and auction objects are less in demand by the public. The occurrence of a lawsuit by the parties is caused by a party who feels aggrieved in the implementation of the auction carried out. The lawsuit material that is often disputed by the parties is Unlawful Acts through the District Court and requests for cancellation of Legal Products resulting from the implementation of auctions, namely Minutes of Auction through the State Administrative Court (PTUN).The author's advice to the KPKNL to increase the intensity of communication with the community so that the public does not hesitate to participate in KPKNL auction activities